Effects of CXCL4/CXCR3 on the lipopolysaccharide‐induced injury in human umbilical vein endothelial cells. Issue 12 (9th May 2019) - Wang, Xiaolin; Zhao, Zhenzhen; Zhu, Kaimin; Bao, Rui; Meng, Yan; Bian, Jinjun; Wan, Xiaojian; Yang, Tao
Abstract: Chemokines and inflammatory response of endothelial cells is crucial in the development and progression of inflammatory disease. Lipopolysaccharide (LPS) is a well‐known factor to trigger inflammatory response and induce damage of endothelial cells. The present study used lipopolysaccharide (LPS)‐treated human vascular endothelial cells (HUVECs) to investigate the function of chemokine CXC chemokine ligand 4 (CXCL4) and its receptor CXC chemokine receptor 3 (CXCR3) in inflammatory‐induced endothelial injury. LPS exposure (50, 100, 200 ng/ml) to HUVECs induced a dose‐ and time‐dependent increase in CXCL4 and CXCR3 expression at both mRNA and protein levels. The LPS‐induced endothelium hyperpermeability was inhibited by the addition of CXCL4 neutralizing antibody. Moreover, the addition of CXCL4 neutralizing antibody abolished the effects of LPS on tight junction (TJ) protein expression (occludin claudin‐4 and Zonula occluden‐1[ZO‐1]) and p38 phosphorylation, which is supported by the observation of increased TJ protein expression and decreased p38 phosphorylation in LPS‐treated HUVECs. SB203580, a p38 inhibitor, protected HUVECs from CXCL4‐stimulated damage. In conclusion, CXCL4/CXCR3, which was enhanced by LPS, may be involved in endothelial proliferation, apoptosis, and permeability via the p38 signaling pathway. Abstract : CXCL4/CXCR3, which was enhanced by lipopolysaccharide, may be involved in endothelial proliferation, apoptosis, and permeability via the p38 signaling pathway.